2016
DOI: 10.1016/j.celrep.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

CARMA3 Is a Host Factor Regulating the Balance of Inflammatory and Antiviral Responses against Viral Infection

Abstract: Host response to RNA virus infection is sensed by RNA sensors such as RIG-I, which induce MAVS-mediated NF-κB and IRF3 activation to promote inflammatory and antiviral responses, respectively. Here, we found that CARMA3, a scaffold protein previously shown to mediate NF-κB activation induced by GPCR and EGFR, positively regulates MAVS-induced NF-κB activation. However, our data suggest that CARMA3 sequesters MAVS from forming high-molecular weight aggregates, thereby suppressing TBK1/IRF3 activation. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 47 publications
(66 reference statements)
1
39
0
Order By: Relevance
“…Remarkably, in the latter study, MALT1 was entirely dispensable for RIG-I-induced NF-B activation, but its role in RIG-I-mediated IFN regulatory factor 3 (IRF3) activation and type I interferon production remains to be determined. In this context, CARD10, another protein known to be engaged in a signaling module with BCL10 and MALT1, was also shown to positively regulate RIG-I-mediated activation of NF-B and proinflammatory cytokine expression in mouse embryonic fibroblasts and lung epithelial cells but to negatively regulate RIG-Imediated activation of IRF3 and type I IFN expression by suppressing oligomerization of the adaptor protein MAVS (57). In agreement, CARD10-deficient mice had a lower viral load and higher production of type I IFN 1 day after intranasal infection with VSV.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, in the latter study, MALT1 was entirely dispensable for RIG-I-induced NF-B activation, but its role in RIG-I-mediated IFN regulatory factor 3 (IRF3) activation and type I interferon production remains to be determined. In this context, CARD10, another protein known to be engaged in a signaling module with BCL10 and MALT1, was also shown to positively regulate RIG-I-mediated activation of NF-B and proinflammatory cytokine expression in mouse embryonic fibroblasts and lung epithelial cells but to negatively regulate RIG-Imediated activation of IRF3 and type I IFN expression by suppressing oligomerization of the adaptor protein MAVS (57). In agreement, CARD10-deficient mice had a lower viral load and higher production of type I IFN 1 day after intranasal infection with VSV.…”
Section: Discussionmentioning
confidence: 99%
“…CARMA3 was identified as one of the key regulators in this process. 105,106 It is a scaffold guanylate kinase-like protein with a caspase recruitment domain and membrane…”
Section: Other Key Players Recently Identified In Influenza Immunopatmentioning
confidence: 99%
“…CARMA3 was involved in the RIG-I-MAVS pathway, and was shown to play a negative role in regulating host antiviral responses, but a positive role in inducing proinflammatory cytokines leading to immunopathology. 105 Other PRRs such as C-type lectin receptors, TLRs, and formyl peptide receptors are also involved in the initial inflammatory responses [107][108][109][110][111] (►Table 1).…”
Section: Tlr7mentioning
confidence: 99%
“…Upon different stimuli, all CARMA proteins can form a complex with BCL10 and MALT1, and the CARMA-BCL10-MALT1 (CBM) complex functions to activate NF-κB signaling (Pomerantz et al, 2002 ; Grabiner et al, 2007 ; Jiang et al, 2011 ). Besides in NF-κB signaling, CBM complex is also involved in antiviral innate immune response by suppressing IRF3-type I IFN expression through inhibiting the formation of MAVS oligomerization in mitochondrion (Jiang et al, 2016 ). CARMA3 was reported to be relatively overexpressed in many tumor cells and associated with the malignant behavior of cancer cells (Li et al, 2012 ; Pan et al, 2016 ).…”
mentioning
confidence: 99%
“…Our previous studies show that overexpressed CARMA3 is K63-linked polyubiquitination, which may regulate NF-κB activation (Jiang et al, 2016 ). To determine how DNA damage regulates CBM complex, we co-expressed CARMA3 together with K48- and K63-linked ubiquitin, and found that DNA damage significantly induced K63-linked polyubiquitination (Fig.…”
mentioning
confidence: 99%